La ontología naturalista de Spinoza como ontología de la pasión - Hoyos Sánchez, Inmaculada (Logos. Anales del Seminario de Metafísica, 2012)
The aim of this paper is twofold. Firstly, it deals with showing that Spinoza´s ontology is naturalistic because it conceives of reality as nature, and, in this way, it combats all form of mystification that presents us the reality as something supernatural and transcendent nature itself. Secondly, it deals with showing, according to characteristic features of Spinoza ´s naturalism, that is, its dynamism and its materialistic elements, that Spinoza´s ontology is an ontology of the passions. The passions are, according to Spinoza´s philosophy, modes of being, finite, human modes of being.